Coffee (Coffea arabica L.) plants’ tolerance to manganese in a nutrient solution - Zabini, André Vinicius; Martinez, Hermínia Emília Prieto; Silva, Camila Andrade (Coffee Science - ISSN 1984-3909, 2007)
Manganese toxicity is one of the most common toxicities among micronutrients, especially in tropical acid soils, affecting crop growth and productivity. The objective of this work was to determine differential tolerance to manganese doses in coffee plants (Coffea arabica L.). Thus, seedlings of 14 coffee plant progenies were subjected to 7,0 and 70,0 μmol L-1 of manganese, for seven months. The experiment was carried out in greenhouse using plastic pots containing aerated and modified Clark solution. A 14 x 2 factorial scheme (14 progenies and two manganese concentrations) arranged in a completely randomized design with three replications was used. At the end of the assay, the growth characteristics of the plants were evaluated. Manganese content was determined in the different leaf dry matter fractions (youngest leaves, oldest leaves and completely expanded leaves). When cultivated with a 70,0 μmol L-1 manganese concentration, the progenies UFV 3880, Mundo Novo 12 CAS, H-518-3-6-1 and H-518-2-10-14 experienced a reduction in growth characteristics, suggesting high sensibility to manganese toxicity, while the progenies UFV 6869 and H-337-13- 3-10 did not present any reduction of the growth characteristics evaluated, demonstrating a high tolerance to manganese toxicity. Similarly, manganese contents in mature leaves were toxic to some progenies, but not to others, demonstrating differences among coffee varietals.